2019
DOI: 10.1021/acs.est.9b01160
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Iodine (127I and 129I) Record in Spruce Tree Rings in the Northeast Qinghai-Tibet Plateau

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 45 publications
2
33
0
Order By: Relevance
“…In the Arctic environment, iodine has recently been identified as a significant source of cloud condensation nucleii (CCN), with the potential to influence clouds formation 3 . Iodine in the atmosphere is increasing globally (3-fold since the 1950s), as independently evidenced by polar and alpine ice core and tree ring measurements, following anthropogenic ozone pollution and global warming [16][17][18] . In the Arctic, a coastal ice core from Greenland revealed that ocean primary productivity controlled atmospheric iodine variability during the Holocene (i.e., last 11,700 years) 19 .…”
mentioning
confidence: 89%
“…In the Arctic environment, iodine has recently been identified as a significant source of cloud condensation nucleii (CCN), with the potential to influence clouds formation 3 . Iodine in the atmosphere is increasing globally (3-fold since the 1950s), as independently evidenced by polar and alpine ice core and tree ring measurements, following anthropogenic ozone pollution and global warming [16][17][18] . In the Arctic, a coastal ice core from Greenland revealed that ocean primary productivity controlled atmospheric iodine variability during the Holocene (i.e., last 11,700 years) 19 .…”
mentioning
confidence: 89%
“…A potential climate relevance arises from the fact that anthropogenic pollution ozone in the troposphere has increased the global iodine source by roughly a factor of 3 since 1950 (38)(39)(40). Ozone reacts with I − at the ocean surface, which results in ozone deposition and the emission of HOI and I 2 to the atmosphere.…”
Section: Iodine In the Anthropocenementioning
confidence: 99%
“…S12) emitted from the oceans (13,44). Ocean iodine emissions have tripled since 1950 (45)(46)(47), and it has been proposed that oceanic emissions of inorganic iodine may increase by ∼20% following Representative Concentration Pathway 8.5 over the 2000-2100 period (30), although the increase in emissions would be much less under different scenarios. Consequently, the future relative contribution of iodine to stratospheric ozone loss may likely be higher than at present, with potential implications in delaying the future closing of the ozone hole, which warrant further investigation.…”
Section: Earth Atmospheric and Planetary Sciencesmentioning
confidence: 99%